Time for fresh thinking on Northern Ireland and Brexit - David Henig (European Centre for International Political Economy (ECIPE), 2022)
The Good Friday / Belfast Agreement became, with considerable efforts over several years from so many involved, a broadly accepted if never fully stable political framework for Northern Ireland. A year after implementation, the prospect of the Northern Ireland Protocol delivering similar results is diminishing. Instead, there is a risk it entrenches divisions in which all sides believe others, not themselves, must be the ones to compromise most. Such divisions around the Protocol have spread beyond the land and sea borders of Northern Ireland, increasingly overshadowing relationships between the UK and the EU, and the UK and the US. These are not in any of their wider interests. Talk of trade wars in Europe cannot strengthen any economy, while the UK's diplomatic relationships with the US remain strained. Finding unity on huge questions like Russia-Ukraine becomes harder against this backdrop. To varying degrees, all of the parties involved in the Northern Ireland Protocol discussions were involved in reaching the 1998 Agreement that ended the 30-year period known as 'the troubles'. Drawing on the lessons from that time and the arrangements they put in place, there is a need for a new political process, outside of technical discussions on trade matters within the Protocol. A new shared endeavour is needed to resolve what otherwise threatens to be a long and damaging Northern Ireland and Brexit stalemate.
Keywords: 330; Brexit; Handel; EU-Staaten; Großbritannien; Nordirland